MENGINTEGRASIKAN PEMBELAJARAN MATEMATIKA BERBASIS BUDAYA BANTEN PADA PENDIRIAN SD LABORATORIUM UPI KAMPUS SERANG - Supriadi, Supriadi; Arisetyawan, Andika; Tiurlina, Tiurlina (Mimbar Sekolah Dasar, 2016)
This study focused on the characteristics of the development of teaching materials, teachers and students in mathematics learning  based on Banten's culture. The Methods which is used in this research are  didactical  Design Research and experimental study, the subject of the study is a second grade of primary school student in the city of Serang  where this research  was taking place in academic year 2015/2016. The study stated that: Characteristics of teachers in mathematics learning  based on Banten’s culture, the teachers have the ability  of meta pedagogical skill in preparing the learning process  which is divided into three stages: before, during and after learning. Meanwhile, before learning the subject, The  Students  have to learn more about Banten’s culture, Also They discussed and solved the problems using it. On the last stage,  the students reflected  their knowledge and  shared their impressions after learning.Keywords: mathematical instruction, Banten Culture, Didactical Design Research.